Green Synthesis of an Activated Carbon-Supported Ag and ZnO Nanocomposite for Photocatalytic Degradation and Its Antibacterial Activities - Taha, Amel (Molecules, 2020)
In this study Ag nanoparticles (AgNPs), ZnO nanoparticles (ZnONPs), and Ag/ZnO nanocomposites were greenly synthesized and loaded on activated carbon via three different routes: simple impregnation, successive precipitation, and co-precipitation. Neem leaf extract was used as a reducing and stabilizing agent. The morphological and structural properties of the synthesized nanocomposites have been examined using different analytical techniques such as XRD, SEM, FTIR, and UV. The antibacterial and catalytic activity of the synthesized nanocomposites were examined and compared. The results showed that AgNPs loaded on activated carbon (Ag/AC) has the best catalytic activity compared to the other nanocomposites, which is attributed to the good dispersal of AgNPs on the surface of activated carbon. Furthermore, AgNPs showed the best antibacterial effect on eight out of 16 tested pathogens. Results also showed that the order of precipitation is an important factor, as both antibacterial activities and photodegradation activities were higher for ZnO/Ag/AC than Ag/ZnO/AC. Furthermore, the co-precipitation method was shown to be better than the successive precipitation method for 4-nitrophenol photodegradation and 14 out of the 16 antibacterial tests performed.